COORDONATE ALE CONSTRUCŢIEI CURICULEI DISCIPLINARE DISCURS DIDACTICO-ŞTIINŢIFIC BAZAT PE CULTURA EMOŢIONALĂ PROGRAMUL DE MASTER METODOLOGIA CERCETĂRII ÎN ŞTIINŢELE PEDAGOGICE - USM ADMIN (Moldova State University, 2008)
The article presents the affective kind of the university scientific communication problems as well as the coordinates of the Didactic and scientific speech based on emotional culture curricular construction in the framework of the Research methodology in pedagogical sciences master program, arguing the necessity of assuring the researchers (experts in education) the development of the scientific communication competence marked by emotional intelligence.